Fatigue Strength Assessment of an Aluminium Alloy Car Body Using Multiaxial Criteria and Cumulative Fatigue Damage Theory - Yiming Shangguan; Wenjing Wang; Chao Yang; Anrui He (Applied Sciences, 2022)
With the rapid development of urban rail transit, metro vehicles have become preferred choices for urban transportation. It is important to accurately evaluate the fatigue strength of a car body to ensure subway safety. A new method based on multiaxial stress criteria and cumulative fatigue damage theory was proposed for the fatigue strength assessment of welded joints of an aluminium alloy head car body subjected to variable cyclic loads. A local coordinate system was established, according to the geometrical characteristics of the weld. Local stresses perpendicular and parallel to the weld seam were obtained to calculate the stress ratio, stress range, and allowable stress value corresponding to the stress component. Then, the fatigue strength utilization of the joints was estimated to determine whether the fatigue strength of the weld met the design requirements. Moreover, the estimated fatigue life of the car body was predicted with cumulative fatigue damage theory. This method considers both the material utilization degree in multiple stress states and the estimated body fatigue life of the car body. The research results provide a reference and a more comprehensive guarantee for the fatigue strength evaluation of a subway car body’s welded structure to ensure vehicle safety.